Three distinct mutational mechanisms acting on a single gene underpin the origin of yellow flesh in peach. (8th August 2013) - Falchi, Rachele; Vendramin, Elisa; Zanon, Laura; Scalabrin, Simone; Cipriani, Guido; Verde, Ignazio; Vizzotto, Giannina; Morgante, Michele
Summary Peach flesh color (white or yellow) is among the most popular commercial criteria for peach classification, and has implications for consumer acceptance and fruit nutritional quality. Despite the increasing interest in improving cultivars of both flesh types, little is known about the genetic basis for the carotenoid content diversity in peach. Here we describe the association between genotypes at a locus encoding the carotenoid cleavage dioxygenase 4 (PpCCD4), localized in pseudomolecule 1 of the Prunus persica reference genome sequence, and the flesh color for 37 peach varieties, including two somatic revertants, and three ancestral relatives of peach, providing definitive evidence that this locus is responsible for flesh color phenotype. We show that yellow peach alleles have arisen from various ancestral haplotypes by at least three independent mutational events involving nucleotide substitutions, small insertions and transposable element insertions, and that these mutations, despite being located within the transcribed portion of the gene, also result in marked differences in transcript levels, presumably as a consequence of differential transcript stability involving nonsense‐mediated mRNA decay. The PpCCD4 gene provides a unique example of a gene for which humans, in their quest to diversify phenotypic appearance and qualitative characteristics of a fruit, have been able to select and exploit multiple mutations resulting from a variety of mechanisms.